Inadequate Nutrient Intakes in Youth of a Remote First Nation Community: Challenges and the Need for Sustainable Changes in Program and Policy. (5th March 2012) - Gates, Allison; Hanning, Rhona M.; Gates, Michelle; McCarthy, Daniel; Tsuji, Leonard J. S.
Abstract : Background . The current study established baseline nutrient intakes of youth and examined the potential for sustainability of a pilot school snack program in the remote First Nation of Kashechewan, Ontario, Canada. Methods . Twenty-four-hour dietary recalls established baseline intakes in grade 6–8 students (n = 43 ). Subsequently, a pilot healthy school snack program was initiated. Dietary recalls were completed one week (n = 43 ) and one year after the program (n = 67 ). Paired Wilcoxon signed-ranks tests were used to detect changes in intakes. Impressions of the teachers (n = 16 ), principal, and students were collected qualitatively. Results . Most youth had dietary intakes below current standards. Although vitamin C (P = 0.024 ) and fibre (P = 0.015 ) intakes improved significantly after one week, these improvements were not sustained over the following year. Program impressions were positive. Conclusion . The need for a nutrition program is clear. While benefits were realized in the short term, improvements could not be maintained. Policy changes are needed to address barriers to sustainability.